Compass or wind chime? An analysis of the draft "strategic compass" of the EU - Markus Kaim; Ronja Kempin (Stiftung Wissenschaft und Politik (SWP), 2022)
In March 2022, the 27 member states of the European Union (EU) want to adopt a 'Strategic Compass' (SC) that is intended to make the Union a provider of international security by 2030 and strengthen its strategic sovereignty. The first draft of this document has been available since mid-November, and it shows serious deficits: strategic fragmentation, over-institutionalization, and diffusion of responsibility remain hallmarks of EU security and defense policy. In the upcoming revision of the compass, Berlin is called upon in particular to clarify its status and set a clear target of ambition. Otherwise, the Strategic Compass is likely to encourage an EU security policy whose motto is 'Everything can be done, nothing must be done.'
Keywords: 320